A Case of Adult-Onset Eccrine Angiomatous Hamartoma-The Comparison with Epithelioid Hemangioma - Mai Nishimura; Yoshiaki Matsushima; Yasuo Nakai; Koji Habe; Akinobu Hayashi; Keiichi Yamanaka (MDPI AG, 2022)
Eccrine angiomatous hamartoma (EAH) is a relatively rare benign skin disease characterized by the proliferation of eccrine sweat glands associated with capillary hemangioma and the proliferation of other skin elements such as adipose tissue, hair, and epidermis. The onset of the disease is usually at birth or in childhood and tends to occur in the extremities of females, but it occurred in an adult male in this case. The patient was a 72-year-old man with a 12 × 12 mm light brown, elastic, slightly firm skin nodule on the flexor aspect of his right forearm. A biopsy revealed enlargement of blood vessels, sweat glands, sweat ducts, and erector spongiosum with both lumen dilation and narrowing, leading to the diagnosis of EAH. The histopathological features of EAH include a marked proliferation of microvessels, epithelial-like changes in vascular endothelial cells (such as enlarged nuclei), and infiltration of inflammatory cells, mainly lymphocytes and plasma cells. In adult-onset cases, EAH can be clinically difficult to distinguish from epithelioid hemangioma (EH), which differs in the predominance of microvascular proliferation and the presence of eosinophils in the infiltrating inflammatory cells. It can also be distinguished from EAH by the negative results of S100 and anti-EMA in immunohistological staining. In the current cases, we were able to differentiate the two cases from characteristic findings on HE staining.